Digital coaching systems in sport: a systematic review of emerging technologies and research gaps for evidence-based coaching - Mario Febrian; Andre Igoresky; Ifdil Ifdil (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Sports coaching has been getting a major overhaul from digital technologies. Things like continuous athlete monitoring, computer vision movement analysis, wearable sensors, and intelligent decision-support systems are all part of it. But even with all this rapid progress, the evidence is still scattered across different fields, sport science, engineering, AI, human-computer interaction. That makes it hard to get a clear picture of how well these tools actually work in real coaching. This systematic review pulled together the current evidence on digital coaching systems. We wanted to see what technological approaches are dominant, how solid the research methods are, and where things should go next. The review stuck to the PRISMA 2020 guidelines. We ran a structured Boolean search in Scopus, looking at TITLE-ABS-KEY fields for studies from 2021 to 2025. Only English-language peer-reviewed journal articles that met predefined inclusion and exclusion criteria were kept. Two independent reviewers screened titles, abstracts, and full texts; any disagreements got sorted out in discussion. Methodological quality got rated using the FICO framework, Focus, Information, Context, Outcome. Then we synthesized the findings through inductive thematic analysis. Out of 986 records initially identified, just 15 studies made it through all the eligibility and quality checks. Four major themes came up: wearable sensing and athlete monitoring, computer vision and markerless motion tracking, intelligent and immersive coaching systems, and analytics-driven decision-support. One thing was clear: technical accuracy is consistently high across these studies. But when it comes to long-term coaching effectiveness, usability, implementation, and ethical governance, the evidence is still thin. That points to a clear need for future research, longitudinal, multi-site, and centered on what coaches actually need.